CT-IGFBP-4 as a Predictive Novel Biomarker of Ischemic Cardiovascular Events and Mortality: A Systematic Review - Abhinav Bhattarai; Pritam Singh Sunar; Sangam Shah; Rajan Chamlagain; Nishan Babu Pokhrel; Pitambar Khanal; Sanjit Kumar Sah; Sujan Poudel; Kapil Belbase; Swati Chand; Rajaram Khanal; Anil Bhattarai (Journal of Interventional Cardiology)
Background and objective. Numerous novel biomarkers have been proposed for the early diagnosis of cardiovascular diseases. Measurement of the carboxyl-terminal (CT) fragment of IGFBP-4, the CT-IGFBP-4, has shown promising efficacy in cardiac risk assessment in various studies. We performed a systematic review of studies that accessed the utility and predictability of CT-IGFBP-4 in different ischemic cardiovascular events. Methods. The electronic databases PubMed, medRxiv, ScienceDirect, and Google Scholar were searched for relevant literature from inception to the 10th of December, 2021. Thus, retrieved literature was screened by title and abstract, followed by full-text screening based on the eligibility criteria. The risk of bias was accessed using the quality in prognostic studies (QUIPSs) tool. The data on cardiovascular outcomes about CT-IGFBP-4 levels were studied and the results were synthesized. Results. Five studies with a total of 1,417 participants were included in our study. The studies reported a low risk of bias. The mean age of the participants was 66.14 and more than 65% were males. Elevated CT-IGFBP-4 levels were associated with poor cardiovascular outcomes and increased mortality in severely ill patients. In contrast, there were no significant findings in the case of stable patients. Sandwich ELISA using lithium-heparin plasma provided a better detection limit of 0.15 ng/ml, low cross-reactivity (<2%), and generated linear results between 12 and 500 ng/ml. Conclusion. CT-IGFBP-4 is an efficient biomarker for the prediction of MACE and mortality in patients with severe ischemic cardiovascular events.